Meme Sejarah Sebagai Media Pembelajaran Sejarah Di SMAN 13 Padang - Aldi Yuherman; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2023)
This research by the lack of use in the history learning process so that learning becomes monotonous. Therefore, it is necessary to develop historical meme learning media that can increase student understanding of historical material. The aimn of this study are (1) to develop historical meme media as a medium for learning history at SMAN 13 Padang. (2) To develop the use of historical memes in history learning for student pf SMAN 13 Padang. The method in this research is to use research and develoment (R & D) methods. The model used is the ADDIE, Analysis, Design, Development, Implementation, Evaluation model, but this research only reached the implementation stage. The subjects of the limited trial were students of class XI IPS 1 of SMAN 13 Padang. Whit the object of the limited trial being historical meme media using cognitive learning theory. The result of the development research is the historical meme media. Based on the results of the validation test of material experts and media expert using a Likert scale with an average valua of 3,5 material validation test and 3,33 media, it can be concluded that the media is very feasible. The results of the praticality test of the teacher show the result whit and average value of 3,33 and the results of the practicality of students whit and average value of 3,18. The conclusion from these result shows that historical meme media is appropriate to be used learning medium.